Percutaneous Radiofrequency Ablation of Small Renal Tumors Using CT-Guidance: A Review and Its Current Role - Haddad, Richard L; Patel, Manish I; Vladica, Philip; Kassouf, Wassim; Bladou, Frank; Anidjar, Maurice (Urology Journal, 2012)
PURPOSE: To provide key evidence-based strategies to improve outcomes of radiofrequency ablation and limit recurrences of small renal tumors. MATERIALS AND METHODS: The literature was searched via OvidSP MEDLINE from 1997 to current using MeSH terms. All levels of evidence and types of reports were reviewed. RESULTS: We comprehensively reviewed technical issues, mechanisms, imaging criteria, ablative success, enhancement within one month, contraindications, oncological efficacy, morbidity rates, and follow-up strategies. CONCLUSION: The technique is safe and effective. Tumors < 2.5 cm are statistically most likely to remain disease-free. Anterior tumors are contraindicated. Strict follow-up is needed to detect failures, most of which occur within 3 months and can be easily salvaged with repeat radiofrequency ablation. Homogeneous enhancement within 1 month is not necessarily a failure, and tends to disappear after 4 to 6 weeks. Multi-disciplinary meetings must occur to discuss each case prior to treatment.